Pengaruh Pengetahuan dan Sikap Terhadap Minat Mahasiswa Menggunakan Quick Response Code Indonesian Standart (QRIS) Pembayaran Digital - Algusri, Jeki; Magdalena, Maria; Hadi, M.Fikry (Akuntansi & Ekonomika, 2024)
The growth of the digital economy and the acceleration of financial inclusion in a nation will be aided by advancements in technology and information technology. Payment of non-cash transactions is one form of implementation. QRIS Indonesia can be used not only by traders with big businesses; students can also use it as a digital payment method. This is the basis of this research to find out students' interest in the application of QRIS as a digital wallet payment technology. Knowledge and attitudes that affect students' interest in using digital payment QRIS are determined in this study. In this research, it can be seen that the use of QRIS has a great influence on knowledge, attitudes and interest in digital payments.